ANALISA YURIDIS KEWENANGAN PENYIDIK PEGAWAI NEGERI SIPIL PADA INSTITUSI PEMADAM KEBAKARAN DALAM INVESTIGASI KEBAKARAN - Jatiur Sinaga (2021)
So far, in the Regulations for the Establishment of Fire Fighting Institutions contained in the DKI Jakarta Governor Regulation Number 264 of 2016 concerning the Organization and Work Procedures of the Fire Management and Rescue Agency, it is stated that one of the tasks of the Fire Department, especially in the ranks of the City/Regency Sub-dept., mandates Fire Investigations. or it can be interpreted as a Fire Investigation, but after the authors have reviewed so far from various sources that have the results of questions and answers and their experience there are still many limitations of Civil Servant Investigators to carry out investigations in the pre-investigation stage and until the fire investigation process, these limitations are generally related to the protection of Civil Servant Investigators themselves and their authority in full processing in investigations. Civil Servant Investigators are certain Civil Servant Officials based on statutory regulations appointed as Investigators and have the authority to conduct criminal investigations. The results of this study are expected to provide input to the parties in determining the extent to which Fire Investigation Arrangements are based on statutory provisions, and position in the function and role of Civil Servant Investigator of Fire Fighting Institutions in the Process of Investigating Fire Occurrence. So that every time a fire occurs, firefighters must be able to carry out fire investigations and not be carried out by other agencies. Therefore, it is very necessary to have a law that regulates the duties, principals, functions, and responsibilities of fire fighting institutions and does not depend on other institutions to carry out fire investigations so that the cause of the fire is not only guesswork but is based on an investigation of facts at the scene of the case.